Rancangan Sistem Smart Home Untuk Mengendalikan Peralatan Rumah Tangga Yang Terintegrasi Website - Faisal, Ahmad; Nuryanto, Nuryanto; Prabowo, Nugroho Agung (Jurnal Komtika (Komputasi dan Informatika), 2022)
The development of automation techniques has an impact on conveniences in people's lives. Nowadays people are busy with all activities and often make the condition of the house, especially the control of electricity and electronics in the house, less attentive, causing waste. This study aims to design a system for monitoring and controlling household electronic equipment with a web-based smart home system. The method used is sometimes an experimental method by implementing nodemcu ESP8266 as a processor to monitor and control household appliances with a website interface as a page for setting and controlling it. It is hoped that this system can make a reference for the development of other automation systems and can be used for energy saving models in the future.